2018
DOI: 10.1002/aet2.10207
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Advanced Practice Providers in Academic Emergency Departments: Best Practices and Considerations

Abstract: As emergency department (ED) visits continue to increase nationwide, the utilization of advanced practice providers (APPs) has been steadily increasing. Academic centers face unique challenges in the inclusion of APP staff into the educational and teaching environment. Effort should be made to both take advantage of and support the educational mission of academic centers while bolstering clinical care provided by APP staff. This paper highlights some of the considerations and challenges in incorporating APPs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…For both PAs and NPs, most postgraduate training occurs as nonstandardized site‐specific on‐the‐job training. At present, there is no standardization for onboarding in EM, which has led health care organizations to create their own standards and on‐boarding processes 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For both PAs and NPs, most postgraduate training occurs as nonstandardized site‐specific on‐the‐job training. At present, there is no standardization for onboarding in EM, which has led health care organizations to create their own standards and on‐boarding processes 14 …”
Section: Methodsmentioning
confidence: 99%
“…At present, there is no standardization for onboarding in EM, which has led health care organizations to create their own standards and on-boarding processes. 14…”
Section: Postgraduate Trainingmentioning
confidence: 99%
“…The logistics of recruiting and credentialing of PA providers were similar to that of hiring non-resident PA providers and was based on institutional guidelines as well as best practices described in literature. 10 The university institutional review board approved our work as an exempted study.…”
Section: Curricular Designmentioning
confidence: 99%
“…Several EM-PA residencies exist, with prior publications outlining best practices in the logistics of some of these programs. 10 Although a recent cross-sectional study of EM-PA residencies identified that 93% of programs were in institutions that also had an EM residency program, it is unclear how the educational programs of their PA residents interacted with their respective MD residents. 2 The aim here was to describe an EM-PA residency collocated and embedded within an existing physician residency and demonstrate the feasibility of this interprofessional approach to EM-PA postgraduate training.…”
Section: Impact/ Effectivenessmentioning
confidence: 99%
“…Our results appear consistent with descriptive studies over the past decade that have noted an increase in APP presence across EDs. 7 Nearly all AACEM-member EDs are employing APPs (98%) and the vast majority of patients seen by APPs also involve attending physicians, ranging from 98% of high-acuity patients to 59% of low-acuity patients.…”
Section: Perceived Impacts On and Opportunities For Resident Educationmentioning
confidence: 99%